Simulation of Motor Speed Regulation Utilizing PID and LQR Control Techniques - Muhammad Izzul Haj; Dimas Eka Saputra; Rama Arya Sobhita; Nugraha, Anggara Trisna (MEIN : Journal of Mechanical, Electrical & Industrial Technology, 2025)
Indonesia is widely regarded as a pioneer in agricultural innovation, with a strong focus on advancing industrial processes through modern control systems. A key challenge in motorized industrial systems lies in ensuring operational precision and efficiency, especially in applications involving automated machinery. This study explores methods to enhance the performance of induction motor control systems by employing advanced techniques. The primary aim is to ensure reliable and accurate regulation of motor speed and position in industrial environments. By integrating electrical and mechanical components, the system is designed for stable and efficient operation. To achieve these objectives, two control approaches Proportional-Integral-Derivative (PID) and Linear Quadratic Regulator (LQR) are applied and analyzed. Simulations and experiments are carried out to evaluate the effectiveness of each method in ensuring motor stability and operational efficiency. The results indicate that LQR demonstrates higher flexibility and resilience, whereas PID offers a straightforward yet efficient control mechanism. This research advances the field of intelligent control systems for industrial use, emphasizing the critical role of sophisticated control strategies in optimizing motor-driven operations across diverse industrial sectors.